Pengaruh Sarana Dan Prasarana Pendidikan Terhadap Kinerja Guru MTs. Negeri 4 Banyuwangi - Nur Hidayati; Ufik Dzuroidah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
This study aims to: (1) To find out about educational facilities and infrastructure in MTs 4 Banyuwangi Sumberberas Muncar Banyuwangi 2018/2019 Academic Year. (2) To find out the performance of teachers in MTs 4 Banyuwangi Sumberberas Muncar Banyuwangi 2018/2019 Academic Year. (3) To determine whether there is an influence of educational facilities and infrastructure on the performance of teachers in MTs 4 Banyuwangi Sumberberas Muncar Banyuwangi 2018/2019 Academic Year. (4) To find out how much influence educational facilities and infrastructure have on teacher performance in MTs 4 Banyuwangi Sumberberas Muncar Banyuwangi 2018/2019 Academic Year. In this study using quantitative descriptive methods with the product momunt technique in the validity test and using regression techniques for data analysis. The population of this study was 45 teachers of MTs Negeri 4 Banyuwangi Sumberberas Muncar Banyuwangi. After analyzing the data collected, it was found that (1) Means and Infrastructure of MTs 4 Banyuwangi Sumberberas Muncar Banyuwangi were very good. (2) Teacher performance in MTs Negeri 4 Banyuwangi Sumberberas Muncar Banyuwangi is very good. (3) There is an effect of the application of management functions on improving the quality of teaching staff of MTs Negeri 4 Banyuwangi Sumberberas Muncar Banyuwangi. (4) the influence of educational facilities and infrastructure on the performance of teachers in MTs Negeri 4 Banyuwangi Sumberberas Muncar Banyuwangi by 39%.